Spring Frost Controls Spring Tree Phenology Along Elevational Gradients on the Southeastern Tibetan Plateau - Wang, Yafeng; Case, Bradley; Rossi, Sergio; Zhu, Liping; Liang, Eryuan; Ellison, Aaron M (My University, 2017)
Temperature is considered to be a main driver of spring phenology, whereas the role of climate extremes (such as spring frosts) has long been neglected. A large elevational gradient of mature forests on the Tibetan Plateau provides a powerful space-for-time ‘natural experiment’ to explore driving forces of spring phenology. Combining 5-yr of in situ phenological observations of Smith fir (Abies georgei var. smithii) with concurrent air temperature data along two altitudinal gradients on the southeastern Tibetan Plateau, we tested the hypothesis that spring frost was a major factor regulating the timing of spring phenology. Onset of bud swelling and leaf unfolding in the study years occurred ≈ 18 or 17 days earlier, respectively, at the lowest (3800 m a.s.l.) elevation relative to upper treelines (4360 or 4380 m a.s.l.). The frequency of freezing events and last freezing date were critical factors in determining the timing of bud swelling along two altitudinal gradients, whereas onset of leaf unfolding was primarily controlled by the onset of bud swelling. This finding provides evidence for detrimental impacts of spring frost on spring phenology, which have been underappreciated in research on phenological sensitivity to climate but should be included in phenology models. It contributes to explain the declining global warming effects on spring phenophases, because climatic extreme events (e.g. spring frosts) tend to increase with warming.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 4101 Climate Change Impacts and Adaptation; 31 Biological Sciences; 41 Environmental Sciences; 13 Climate Action